MORPHOLOGICAL COMPARISON OF NUMERAL SYSTEMS IN INDONESIAN AND TAGALOG: AUSTRONESIAN ROOTS AND COLONIAL INFLUENCES - Aqromi, Nur Lailatul; Espejo, Rommel V (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
Numeral systems are essential for understanding the structure and evolution of languages, as they reflect cognitive processes and are deeply shaped by historical and cultural influences. This study examines the numeral systems of Indonesian and Tagalog, two Austronesian languages, focusing on the morphological processes involved in numeral formation. Despite sharing a common linguistic ancestry, the numeral systems of these languages differ significantly due to various historical and cultural factors, including the impacts of colonization. The research employs a descriptive-qualitative approach, utilizing contrastive analysis to compare the morphological structures of numerals in both languages. Data were collected from literary texts, dictionaries, and language corpora in both languages, and the analysis involved distributional, comparative, and contextual methods. Additionally, consultations with native speakers helped verify numeral usage and clarify any ambiguities. Findings reveal that while both languages use a decimal numeral system, Indonesian generally employs simpler affixation patterns, such as the prefix "se-" in numerals like "seratus" (one hundred) and "seribu" (one thousand). In contrast, Tagalog incorporates more complex structures, often using bound morphemes like "isang-" (one) and "limang-" (five) for larger numbers, such as "isang daan" (one hundred) and "limang libo" (five thousand). The influence of colonial history is evident in both languages, with Tagalog borrowing extensively from Spanish, as seen in numerals like "mil" (thousand) and "milyon" (million), while Indonesian draws influence from Sanskrit and Dutch. The study also highlights the use of reduplication, which is more common in Tagalog, especially in informal contexts, whereas it is rarely used in Indonesian numerals. These findings provide insights into how the numeral systems of Indonesian and Tagalog have evolved differently despite their shared Austronesian roots, shaped by distinct socio-historical contexts. This research contributes to the field of contrastive linguistics and offers a deeper understanding of how external influences, such as colonialism, have shaped the structure of numeral systems in both languages. It also opens avenues for future research on numeral systems in other Austronesian languages.